Analisis Kemampuan Penalaran Matematis Siswa SD Kelas IV Pada Materi Bilangan Bulat : Studi Kasus di SD Pasucen 02 - Diah Fatmasari; Nabila Khoirunnisa; Lovika Ardana Riswari (Universitas Muhammadiyah Kuningan, 2023)
The purpose of this study was to find out and analyze students' mathematical reasoning abilities through integer problems. This research uses a qualitative approach with a case study approach. Data collection technique using purposive sampling. Out of 20 students in grade IV SD Pasucen 02, only 3 students were used as informants, selected based on criteria of high, medium and low ability. The research provided mathematical reasoning questions which were analyzed based on the results and student answers. The results showed that 1 student met the high ability criteria, 1 student met the medium ability criteria, 1 student met the low ability criteria.